Prevalence of different sleep problems in patients with respiratory diseases presented to a respiratory outdoor clinic: A descriptive analysis - Arup Kumar Halder; Arpita Halder Chatterjee (The Journal of Association of Chest Physicians, 2023)
Introduction: A patient with compromised respiratory system due to some diseases, may have disturbed sleep to a great extent. It has been proved in various community based epidemiologic studies. Though most of such studies available had concentrated on single respiratory disease like Chronic Obstructive Pulmonary Disease (COPD) or Asthma in the community. But such studies are hardly available for patients attending a respiratory clinic, where all respiratory ailments were evaluated with concurrent sleep problems. The present study is one such. Methods: Total 163 patients were screened and among them 100 were selected as the study group. The patients were enquired with a standard questionnaire provided to them. In addition, they were given separate questionnaire as STOP BANG, Insomnia Severity Index Score, RLS questionnaire. Those persons with STOP BANG > 5, were also advised for a polysomnography (PSG), if not already done. Descriptive statistical analysis has been carried out in the present study. Results: The present study is a cross-sectional depiction of relationships between various respiratory diseases and sleep problems. As per this study, most patients were asthmatic and commonest sleep problem was OSA. A subgroup analysis was done to determine the significance of difference of various parameters between the three groups of asthmatic patients, patients having COPD and the “Other” group. Discussion: Subjective sleep problems were significantly more in Asthma group than COPD group (P < 0.0362). The mean STOP BANG was more in COPD group than the Asthma group (P < 0.0301). Though OSA was the commonest sleep problem between the three groups, but the prevalence was not statistically significant between them. More patients in the COPD group had insomnia, but it was not statistically significantly more than in Asthma group. Sleeping pill use was significantly more in COPD group than the Asthma group (P < 0.0039). Conclusion: Sleep problems are common in patients with respiratory diseases and OSA is the most common problem according to the present study. Asthma patients had more subjective sleep problems. Sleeping pill use was more common in COPD patients instead of having less subjective sleep complaints than asthma patients.